The Self-Regulating Jury in the Field of Interactive Advertising - López Jim´énez, David; Dittmar, Eduardo Carlos; Vargas Portillo, Jenny Patricia (Law, State and Telecommunications Review, 2023)
[Purpose] Electronic advertising and commercial communications may sometimes violate existing regulations, resulting in unlawful advertising. To address this issue, Spain created an Advertising Jury to resolve disputes in this area. [Methodology/Approach/Design] The Spanish and European regulations will be analyzed in terms of regulation and self-regulation mechanisms. Self-regulation instruments are a suitable complement to current legal regulations. [Findings] Self-regulation mechanisms can be triggered by Autocontrol’s Advertising Jury when an instance of advertising has violated one or more rules of the relevant code of ethics. This organisation is a recognised moral authority in the field and an extrajudicial mechanism for settling disputes concerning interactive advertising. Although it normally adjudicates cases in which the parties have already voluntarily committed to complying with its decisions, it also adjudicates cases involving third parties or non-member companies. [Practical Implications] Self-regulatory initiatives in the field of interactive advertising exist at both the European Union (EU) and national levels. One such initiative implemented at a national level stands out as a positive example for others: Spain’s Autocontrol. [Originality/Value] The purpose of self-regulation is to try and bridge the gap between the law’s minimum requirements and the maximum level of ethical behaviour for online advertising. This should not be achieved through coercion but through the free and voluntary dedication of those involved.